FEATURES OF INTESTINAL TOXICOSES IN CHILDREN OF EARLY AGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
As shows experience, in the standard techniques of diagnostics and treatment of intestinal toxicoses at children (at their application' in conditions of a hot climate) entering some specifications concerning first of all features rehydration of therapy, and also of some the organizational moments is necessary. The last are especially important, as the combination of a hot climate and desease intestinal infections with some social factors (high birth rate, high densities of children in age structure of the population, residing of 2/3 children at a countryside) demand concrete recommendations both for practical doctors, and for organizers of pediatric service.